Fotografia jako jeden z czynników procesu medialnej kreacji rzeczywistości w „kulturze budowania na nieufności” i zaniku zdolności do uprawiania dialogu. Refleksje na przykładzie dziennikarstwa prasowego - Pastwa, Rafał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Photography is one of the factors for the process of media creation of reality. It has a great importance in the ‘culture of building the distrust’. The unbounded usage of photography deepens difficulties in dialogue. Photography used in traditional and new media should go over revolution of re-humanization or re-personalization. But it can only be achieved by a change in the model of integration. Without such attempts, photography will still remain just a product for consumption and the easy tool for creation of reality.